Rewriting Identity: Gender, Memory, and Cultural Politics in Modern World Literature - Umi Salamah; Teddy Oswari; Erni Hastuti; Nurwakhid Muliyono (Yayasan Adra Karima Hubbi, 2026)
Background. Modern world literature has increasingly become a critical site for negotiating identity in the context of shifting gender relations, contested memories, and evolving cultural politics. Literary texts produced in diverse sociopolitical contexts reflect ongoing struggles over representation, power, and belonging, particularly as global and local forces intersect to reshape individual and collective identities. Purpose. This study aims to examine how modern world literature rewrites identity through the interconnected lenses of gender, memory, and cultural politics, highlighting literature’s role in challenging dominant narratives and rearticulating marginalized voices. Method. The study employs a qualitative interpretative approach using comparative literary analysis informed by feminist theory, memory studies, and cultural criticism. Selected literary works from different cultural and geopolitical contexts are analyzed through close reading to identify recurring themes, narrative strategies, and ideological positions. Results. The findings reveal that literary narratives reconstruct identity by destabilizing fixed gender norms, reworking personal and collective memory, and contesting hegemonic cultural discourses. Memory functions as a narrative tool for resistance, while gendered experiences shape alternative representations of history and power. Literature emerges as a space where cultural politics are negotiated through storytelling and narrative form. Conclusion. This study concludes that modern world literature plays a transformative role in rewriting identity by integrating gender, memory, and cultural politics, thereby contributing to more inclusive and pluralistic understandings of contemporary social realities.